THE INFLUENCE OF FINANCIAL PLANNING AND REALIZATION ON BUDGET EFFECTIVENESS AT CLASS D REGIONAL PUBLIC HOSPITAL JATISAMPURNA - Yuliani, Anne; Rangkuti, Zulkifli; Nurmansyah (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This study aims to analyze the influence of financial planning and realization on budget effectiveness at Class D Jatisampurna Regional General Hospital. The background of this study is based on the importance of financial planning and realization in increasing budget effectiveness at Class D Jatisampurna Regional General Hospital. The method used in this study is a quantitative method using a survey method, a research method that involves data collection, analysis, and interpretation that will be used for the study. The results of the study indicate that there is an influence of financial planning and realization on budget effectiveness at Class D Jatisampurna Regional General Hospital both simultaneously and partially, the magnitude of the influence is able to explain the dependent variable by 42.2%; the remaining 57.8% is explained by other variables not included in this study.